Contrasting wood anatomy drives divergent xylogenesis and climate responses in 10 warm-temperate trees - Zhang, Yiping; Zhai, Xiaoli; Lu, Gengxin; Bai, Hanwei; Chen, Jiao; Xu, Junliang; Tian, Yaowu; Pederson, Neil (Frontiers in Plant Science, 2026)
Wood formation is crucial for understanding trees response to environmental conditions and assessing climate change impacts on carbon and water cycles. Nevertheless, species-specific differences in intra-annual radial growth dynamics remain incompletely understood. In this study, we monitored the xylogenesis, its relationships with climatic factors, and leaf phenology in 10 coexisting tree species representing contrasting wood anatomical types under warm-temperate conditions using microcoring techniques from March to December 2018. Our results showed that: (1) Semi- and ring-porous species initiated wood formation earliest (early March) and exhibited the fastest growth rates. In contrast, diffuse-porous species started xylem growth latest (late March) but completed xylogenesis earlier (early November) due to accelerated growth, while conifers maintained slower growth rates over extended growing seasons. (2) Deciduous ring-porous trees and evergreen conifers exhibited delayed leaf out relative to xylem growth, whereas diffuse-porous species initiated leaf development earlier than wood formation, highlighting differences in carbon allocation. (3) Responses to climate differed between coniferous and broadleaved trees: xylem growth of conifers correlated positively with air temperature, while broadleaved trees were primarily driven by precipitation, reflecting wood-type differences in drought sensitivity. Moreover, photoperiod effects varied among wood types, showing negative correlations for conifers and diffuse-porous species but positive correlations for (semi-)ring-porous species. These findings demonstrate distinct differences in xylogenesis between coniferous and broadleaved trees, enhancing our understanding of wood formation in angiosperms. Exploration linkages between wood formation and leaf phenology is essential for predicting species-specific responses to climate change and improving global vegetation carbon models.